Biodesulfurization of high-sulfur oil from the Karazhanbas field of Kazakhstan with deep eutectic solvents - A.O. Akimbek; G.A. Jamalova; A.K. Yernazarova; G.K. Kaiyrmanova; B.K. Yelikbayev; M.C. Pagano; A.G. Zazybin; Kh. S. Rafikova (Heliyon)
The Karazhanbas oil field in the Mangystau region of Kazakhstan contains high-sulfur oil (1.6–2.2 %). It is known that sulfur negatively affects the operational properties of petroleum products, causes the corrosion of pipelines, and adversely affects the environment and the human body. Therefore, the development of biodesulfurization technology, taking into account local features, is relevant for this field. The purpose of the study is to develop biodesulfurization of high–sulfur oil from the Karazhanbas field in Kazakhstan using deep eutectic solvents. Research objectives: isolation of sulfate-oxidizing and sulfate-reducing bacteria from the studied oils; identification of isolated bacteria; study of the effect of heavy metal Cr(VI) and sulfur on microbial activity; testing of native strains for the potential for desulfurization of crude oil. The research methodology was based on the application of the Koch methods to determine the total number of microorganisms; light microscopy – for the study of microbiological preparations; genetic identification of bacteria based on the analysis of the nucleotide sequence of a fragment of the 16S rRNA gene; synthesis of deep eutectic solvents; testing of isolated bacteria – for sensitivity to Cr (VI), for the ability of microorganisms to use hydrocarbons of high-sulfur oil, for activity in sulfur-containing crude oil, for determination of the mass fraction of sulfur. From 12 aerobic bacterial cultures isolated from oil samples, 9 strains with active and moderate growth in a medium with high-sulfur oil were selected during testing, followed by two strains (Bacillus paramycoides SFN-1, Bacillus cereus SFN-2), which were the most resistant to Cr (VI) and two strains (Bacillus cereus SFN2, Bacillus thuringiensis SFN3), which have shown sulfur-oxidizing abilities. The native bacterial strains selected during the study showed high disulfurization activity without the addition of deep eutectic solvents (hereinafter referred to as DES) (Bacillus thuringiensis SFN3), with the addition of DES-1 (Bacillus cereus SFN2) and with the addition of DES-2 (Bacillus thuringiensis SFN3). As a result of a comparative analysis of microbial desulfurization processes, it was found that the highest biodesulfurization rate at the end of the experiment was recorded in cultures of Pseudomonas aeruginosa B-5807 (96.3 %), Bacillus thuringiensis SFN-3 (96.1 %), and Rhodococcus erythropolis AC 1039 (96 %).